The Influence of Pricing and Promotion in Online Advertising on Purchase Interest of Wedding Packages at Alila Villas Uluwatu - Maharani, Putu Ayu Yoga; Suastini, Ni Made; Pitanatri, Putu Diah Sastri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of pricing and promotion on online advertising on the interest in buying wedding packages at Alila Villas Uluwatu. This study was conducted on 100 respondents through the distribution of questionnaires with a Likert scale. Data analysis techniques used in this study are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, t-test, f-test and Determination Coefficient using the SPSS application. The results of the study showed that there was a positive and significant influence of price and online advertising on the interest in buying wedding packages at Alila Villas Uluwatu. The results of this study indicate that the Price Variable (X1) and Online Advertising (X1) have a positive and significant effect simultaneously on the interest in buying (Y) wedding packages at Alila Villas Uluwatu. This is based on the results of the F test and multiple linear regression, namely the number of Fcount values> Ftable, which is 22.415> 3.94 with a percentage of influence of 64.9% with a significance value of 0.00 <0.05.